Calculation of direct DNA damages by a new approach for carbon ions and protons using Geant4-DNA. (February 2021) - Ahmadi Ganjeh, Zahra; Eslami-Kalantari, Mohammad; Ebrahimi Loushab, Mahdy; Mowlavi, Ali Asghar
Abstract: A simulation to predict DNA damages due to 114.2 MeV/u carbon ions and 62 MeV protons at different depths was performed by a new approach to make a comparison between those different beams. An atomic model of DNA was used to build the different levels of DNA organization in the cell nucleus. A new damage diagnostic algorithm was designed to identify break yields and has been used with the Geant4 toolkit. The single strand break (SSB) ratios for carbon ions compared to proton were 18.5 and 19 at 5 mm and 30.7 mm depth in water respectively. For Double-Strand Breaks (DSBs) the ratios were higher and they varied from 27 at 5 mm to 55 at the Bragg peak depth. The DSB yields for the same depths of carbon ion and proton beams were evaluated. The results indicated that the entrance DSB yield were 0.84 and 1.19 (GyGbp) −1 (at 5 mm depth) for protons and carbon ions, respectively, while at the Bragg peak depth were 1.15 and 3.11 (GyGbp) −1 . It has been found that the DSB yield at 5 mm for the carbon beam was about 1.4 times higher than for the proton beam and regarding the Bragg peak depth, this ratio was 2.7. Our new damage diagnostic algorithm can help the identification of breaks. Also, results confirmed that carbon ions are more effective in biological effects than protons. Highlights: Energy spectra of protons and carbon ions were calculated at different depths. Different organizational levels of a DNA atomic model have been constructed. A new method was used to identify DNA breaks. Relative dose, SSB and, DSB due to the protons and carbon ions were estimated. Carbon ions and protons DSB yields varied of 0.84–1.19 (GyGbp) −1 and 1.15 to 3.11 (GyGbp) −1 respectively.